2010
DOI: 10.1007/s00268-010-0846-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Minimally Invasive Thyroidectomy (eMIT): A Prospective Proof‐of‐Concept Study in Humans

Abstract: The experimental development of the eMIT technique has led to its first clinical application in humans. In this prospective proof-of-concept study in humans, the thyroid gland was reached via the transoral endoscopic approach in an anatomically defined layer without any relevant damage to vessels. Limitations to this technique are determined by specimen volume (up to 30 ml) and nodule size (up to 20 mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
120
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(129 citation statements)
references
References 43 publications
0
120
0
6
Order By: Relevance
“…The patient had no complications except for minimal neck swelling and hematoma. Given the initial positive experience with eMIT, a prospective clinical study was conducted in eight patients undergoing total and subtotal thyroidectomies (17). Three cases were converted to open due to large tumor size.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The patient had no complications except for minimal neck swelling and hematoma. Given the initial positive experience with eMIT, a prospective clinical study was conducted in eight patients undergoing total and subtotal thyroidectomies (17). Three cases were converted to open due to large tumor size.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…These incisions can all be placed in the oral vestibule (14) or a combination of oral vestibular and mouth floor incisions can be used (15,16). The procedure can be performed endoscopically (17) or robotically (18) depending on surgeon preference and expertise. Two recent clinical studies have indicated that transoral thyroidectomy can be safe and feasible (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, intended to develop a new surgical approach allowing a scarless access for mediastinal lymph node biopsies. Evidence for such a procedure came from head and neck surgeons who evolved a transoral endoscopic access route for resection of the thyroid some years ago (10)(11)(12). Based on these finding we established this access route for mediastinal lymph node biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…As per my knowledge, the vestibular approach has only been implemented to resect the thyroid gland , with the clinical application of transoral transvestibular endoscopic approach in the surgical removal of the thyroid gland being reported for the first time by Wilhelm et al 1 Transoral endoscopic thyroidectomy vestibular approach (TOETVA) is currently in use in various institutions. TOETVA has been proposed, introduced and clinically performed in various countries including South Korea, Thailand, India, China, Taiwan, Singapore, USA, Mexico, Japan, Ecuador and Italy.…”
mentioning
confidence: 99%
“…TOETVA has been proposed, introduced and clinically performed in various countries including South Korea, Thailand, India, China, Taiwan, Singapore, USA, Mexico, Japan, Ecuador and Italy. [1][2][3][4] We present our opinion on the clinical procedure of TOETVA. The surgical procedure is carried out using a three-port technique at the oral vestibule, by placing one 10-mm port for a 30° endoscope and two additional 5-mm ports for the dissecting and coagulating instruments.…”
mentioning
confidence: 99%